MAIN FEED MYCOTOXICOSES IN LIVESTOCK FARMING AND METHODS FOR THEIR DETECTION - Komiljonovich, Komiljonov Kamol; Buriyevich, Ibragimov Furqat; Muxitdinovich, Do‘skulov Voxidjon; Xasanovich, Xamrayev Asqar (Research Focus International Scientific Journal, 2026)
The article analyzes mycotoxicosis occurring in livestock farming as a result of feed contamination with mycotoxins. It describes the acute and chronic forms of the disease, clinical signs, pathoanatomical changes, diagnostic methods, as well as treatment and prevention measures. Additionally, information on modern laboratory methods for detecting mycotoxins is provided.